Recent Progress on Semiconductor Heterojunction‐Based Photoanodes for Photoelectrochemical Water Splitting - Li, Shengnan; Xu, Weiwei; Meng, Linxing; Tian, Wei; Li, Liang (Small science, 2022)
For photoelectrochemical (PEC) water splitting, the utilization of semiconductor heterojunctions as building blocks for photoanodes allows for high light absorption, effective charge separation, and superior redox capability, greatly boosting the solar energy conversion efficiency. This review mainly focuses on the construction of heterojunction photoanodes, improvement strategies of carrier transmission, and their application in PEC water splitting. First, a series of carrier dynamics characterization methods are introduced to reveal the principle and significance of promoting carrier transport in heterojunctions. Then, from the perspective of the mechanism of promoting the separation and transport of charge carriers, several strategies are summarized and analyzed, including the micro/nanostructure, energy band structure, photothermal effect, piezoelectric effect, pyroelectric effect, ferroelectric effect, and intermediate layer. Finally, the challenges and opportunities for heterojunction photoanodes in PEC reactions are explained clearly, which points the way forward for the development of heterojunctions. This review mainly introduces recent advances on the construction of heterojunction photoanodes, improvement strategies of carrier transmission, and their application in photoelectrochemical (PEC) water splitting. Finally, a view of the future directions in this field is provided. This review has certain guidance and reference significance for research on heterojunction photoanodes.